Early Decompression (<8h) versus Delayed Surgical Management Improves Functional Outcome after Traumatic Cervical Spinal Cord Injury. Issue 1 (April 2016) - Grassner, Lukas; Wutte, Christof; Klein, Barbara; Mach, Orpheus; Riesner, Silvie; Panzer, Stefanie; Vogel, Matthias; Högel, Florian; Bühren, Volker; Strowitzki, Martin; Maier, Doris; Vastmans, Jan
Introduction: Traumatic cervical spinal cord injury affects the individual in a multi-faceted way. Early decompression of the spinal canal is recommended. The optimal time point for this intervention has been under debate for decades. This study compares a variety of neurologic, radiologic and functional outcome parameters between patients after early (<8 hour) versus delayed decompression. Materials and Methods: We performed a retrospective analysis at the Center for Spinal Cord Injuries (Trauma Center Murnau, Germany), an over-regional level-I trauma center. Follow-up data was collected prospectively for one year after injury, according to institutional and international consensus criteria. We included data acquired over a 10-year period (2004 – 2014). We only analyzed patients over 18 years with traumatic cervical spinal cord injury without concomitant extremity injury, traumatic brain injury or central cord injuries. Results: We identified 70 patients (59 males), who met in- and exclusion criteria. Out of this population, 35 patients were decompressed within the first 8 hour (average: 4.36 hour after the insult) (= early group). After one year, patients from the early group showed a significantly higher gain in total motor score (TMS) points and upper extremity motor score (UEMS) points. Additionally, this patient cohort showed significantly better grades on the American Spinal Injury Association Impairment Scale (AIS) and a significantly higher AIS conversion rate. Furthermore, they were more likely to experience a significant greater difference in the Spinal Cord Independence Measure (SCIM) within the follow-up period. Conclusion: This study shows that an early surgical decompression not only leads to higher AIS conversion rates, but – most importantly – also to a better functional outcome (as indicated by the SCIM score).